Pengaruh Profitabilitas, Likuiditas, Pertumbuhan Laba, dan Struktur Modal terhadap Kualitas Laba - Lestari, Muntaz Yuni; Fitriastuti, Lucia Ika (Kajian Ekonomi dan Bisnis, 2025)
This study aims to examine the effect of profitability, liquidity, earnings growth, and capital structure on earnings quality in Consumer Non-Cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. The research method used is a quantitative approach with multiple linear regression analysis techniques. The data used is secondary data obtained from the financial statements of companies listed on the IDX. The research sample was selected using purposive sampling method with a total sample size of 39 companies over a three-year period, so that the total observations used were 117. The results showed that profitability (ROA) partially affects earnings quality. Liquidity (CR) partially has no effect on earnings quality. Earnings growth (GP) partially has no effect on earnings quality. Capital structure (DER) partially has an influence on earnings quality. Simultaneously profitability, liquidity, earnings growth, and capital structure affect earnings quality